2019
DOI: 10.1186/s12935-019-0983-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of YKL-40 in solid tumors: a meta-analysis of 41 cohort studies

Abstract: Background Serum/plasma YKL-40 can be a useful index that is associated with tumor development. However, the prognostic value of serum/plasma YKL-40 in patients with solid tumors is still unclear. We aimed to utilize the existing literature to investigate the prognostic value of serum/plasma YKL-40 in solid tumors. Methods An extensive literature search for relevant studies was conducted with the Embase, Medline and Web of Science da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…A previous meta-analysis showed that elevated circulating levels of YKL-40 were significantly related to poor survival in cancer patients [7]. Certain studies have examined the prognostic implication of YKL-40 tissue expression in patients with solid tumors, but these studies have yielded inconsistent results [8][9][10][11][12][13][14][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis showed that elevated circulating levels of YKL-40 were significantly related to poor survival in cancer patients [7]. Certain studies have examined the prognostic implication of YKL-40 tissue expression in patients with solid tumors, but these studies have yielded inconsistent results [8][9][10][11][12][13][14][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…YKL-40 is considered to play a role in cancer through the process of inflammation surrounding the tumor cells, angiogenesis, and extracellular matrix remodeling [5,6]. According to a recent meta-analysis based on 41 cohort studies with 7762 patients, a high YKL-40 serum/plasma level is correlated with a poor prognosis in patients with solid tumors [7]. Previous studies have shown that YKL-40 tissue expression may serve as a useful prognostic biomarker for solid tumors, such as glioma, ovarian cancer, breast cancer, lung cancer, urologic neoplasm, thyroid carcinoma, and gastric cancer [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Chitinase 3 like 1 (YKL-40/CHI3L1) protein is a member of chitinase family. The elevated expression of YKL-40 is observed in many malignant tumors, which drives tumor growth, angiogenesis and metastasis [ 4 , 5 ]. Previous studies suggest that YKL-40 is up-regulated in the serum and endometrial carcinoma samples of EC patients, and correlates with a poor prognosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…YKL-40 is secreted by tumour cells, such as colon cancer cells, and by tumour-associated macrophages [31], and promotes cancer proliferation and inflammation [32]. Elevated YKL-40 expression in tumours and in the circulation is associated with poor prognosis in various tumour types, including CRC [32][33][34].…”
Section: Introductionmentioning
confidence: 99%